"Rebecca Schneider's Performance Studies Remains" (Mantichora. Italian Journal of Performance Studies, 2020)
This is the transcript of a video-interview I realized with Rebecca Schneider, Professor of Theatre and Performance Studies at Brown University, in May 2012. In this conversation Professor Schneider talks about her work as a Performance Studies scholar and the specific focus of her research interests. By thinking critically about certain aspects of this discipline, above all in relation to Theatre Studies, she underlines the dialogue between performativity and theatricality, as well as the importance of a certain kind of historiography in Performance Studies research methodology. Moving from the ontology of Performance Studies to the ontology of performance, she finally focuses on the idea that performance does not disappear, as she explains in her most recent book, “Performing Remains”.